SPE Latin American and Caribbean Petroleum Engineering Conference 2015
DOI: 10.2118/177228-ms
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Completion Design for Deep Geothermal Wells

Abstract: Harnessing geothermal energy faces many of the challenges encountered in the exploration and production of oil and gas. Deep drilling is a necessity to attain sufficiently high temperatures for successful recovery of unconventional geothermal energy, such as in Enhanced (or Engineered) Geothermal Systems (EGS). The challenge of deep geothermal exploitation is comparable to that posed by high-pressure, hightemperature oil and gas projects. Accessing such deep targets, and the need for suitable well completions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In addition, for geothermal wells that have low permeability, hydraulic fractures are created to increase productivity. Temperature difference between the injected water and reservoir induce significant structural damage of both casing and cement (Okech et al, 2015.) Also, indicated that the main corrosion agent in almost every geothermal well is CO2 -which when it encounters water or steam, forms carbonic acid that leads to metal corrosion. This can be divided into two principal forms of CO2 corrosion: mesa attack (localised CO2 corrosion) and pitting.…”
Section: Hpht and Geothermal Wellsmentioning
confidence: 99%
“…In addition, for geothermal wells that have low permeability, hydraulic fractures are created to increase productivity. Temperature difference between the injected water and reservoir induce significant structural damage of both casing and cement (Okech et al, 2015.) Also, indicated that the main corrosion agent in almost every geothermal well is CO2 -which when it encounters water or steam, forms carbonic acid that leads to metal corrosion. This can be divided into two principal forms of CO2 corrosion: mesa attack (localised CO2 corrosion) and pitting.…”
Section: Hpht and Geothermal Wellsmentioning
confidence: 99%
“…While solutions to enhance the heat exchange between the heat-carrying fluid and the ground in shallow BHE systems have been extensively presented in the literature [39], less is known regarding the improvement of downhole heat exchange characteristics in thermally-boosted, deep BHE systems. Following preliminary results [40], a numerical model was therefore built as part of this study to assess the bulk thermal potential associated with the deep BHE concept of Fig. 17 when extrapolated to the most challenging environment, which -for some regions in the world -may represent the only target for temperatures high enough to generate electrical power.…”
Section: Single-well (Closed Loop) Numerical Model: Bhe With Conductimentioning
confidence: 99%